2022
DOI: 10.1039/d2cy00129b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of catalytic NOx reduction mechanism in an electric field at low temperatures

Abstract: We found that Pd-supported catalysts exhibit high TWC activity when a DC electric field is applied, even at temperatures lower than 473 K, and the reaction mechanism has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, the degree of slip upon electrification is 58% less than that during heating, supporting the hypothesis that the reactivity of C 3 H 6 is improved by electricity. Similarly, Sekine’s groups , also reported the promotion of the applied electric field to C 3 H 6 activation through partial oxidization by surface lattice oxygen into oxygenated species for feasible NO reduction.…”
Section: Resultsmentioning
confidence: 99%
“…However, the degree of slip upon electrification is 58% less than that during heating, supporting the hypothesis that the reactivity of C 3 H 6 is improved by electricity. Similarly, Sekine’s groups , also reported the promotion of the applied electric field to C 3 H 6 activation through partial oxidization by surface lattice oxygen into oxygenated species for feasible NO reduction.…”
Section: Resultsmentioning
confidence: 99%
“…We have already established a purification technique that allows very high NO conversion and N 2 selectivity, even at low temperatures, by the combination of catalyst and electric field. 16,17 In this study, a novel NSR process using a Pt–BaO/CeO 2 catalyst was shown to convert accumulated NO x to N 2 efficiently, even at low temperatures of 423 K and under lean burn conditions.…”
mentioning
confidence: 90%